2016
DOI: 10.1021/acsami.6b08400
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Multifunctional Dendritic Mesoporous Silica Nanoparticles to Load Curcumin and Enhance Efficacy for Breast Cancer Therapy

Abstract: Breast cancer is the primary reason for cancer-related death in women worldwide and the development of new formulations to treat breast cancer patients is crucial. Curcumin (Cur), a natural product, exerts promising anticancer activities against various cancer types. However, its therapeutic efficacy is hindered as a result of poor water solubility, instability, and low bioavailability. The aim of this work is to assess the curative effect of a novel nanoformulation, i.e., Cur-loaded and calcium-doped dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 68 publications
1
77
0
Order By: Relevance
“…Here, we analyzed the cell-cycle distribution of MDA-MB-231 and LO2 cells, incubated with free CUR and nanoparticles (MSN/CUR, MSN/ CUR-PEI, MSN/CUR-PEI-FA and MSN/CUR-HA) at 10 lg/mL for 24 h, using propidium iodide staining and flow cytometry ( Figure 10). Free CUR and MSN/CUR induced the G2/M phase cell cycle arrest, as previously reported [25,38]. MSN/CUR-HA and MSN/CUR-PEI-FA also affected the cell-cycle distribution of MDA-MB-231 cells, with the latter showing a greater effect.…”
Section: Cell-cycle Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…Here, we analyzed the cell-cycle distribution of MDA-MB-231 and LO2 cells, incubated with free CUR and nanoparticles (MSN/CUR, MSN/ CUR-PEI, MSN/CUR-PEI-FA and MSN/CUR-HA) at 10 lg/mL for 24 h, using propidium iodide staining and flow cytometry ( Figure 10). Free CUR and MSN/CUR induced the G2/M phase cell cycle arrest, as previously reported [25,38]. MSN/CUR-HA and MSN/CUR-PEI-FA also affected the cell-cycle distribution of MDA-MB-231 cells, with the latter showing a greater effect.…”
Section: Cell-cycle Analysissupporting
confidence: 85%
“…The folate receptor is a tumour-associated protein overexpressed in more than 40% of human tumours, including breast cancer [23,24]. CUR-loaded dendritic MSN modified with folic acid (FA) showed a good dispersion in aqueous solutions and were effectively targeted to MCF-7 human breast cancer cells [25]. We developed a polyethyleneimine (PEI)-FA complex conjugated with MSN via disulphide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on cancer therapy in recent years have revealed that CM can cause apoptosis signals in various cancers. [23][24][25] As shown in Figure 5B and D, cells treated with CM-SF NPs showed a higher percentage of apoptosis (~23%) than those treated with 5-Fu (~16%). This indicates that CM-SF NPs had better apoptotic cell-induction potential than 5-Fu.…”
Section: Induction Of Cell Apoptosismentioning
confidence: 83%
“…The Ayurvedic drug curcumin (Cur) was also effectively loaded on DFNS, named dendritic mesoporous silica nanoparticles (DMSNs) . Curcumin derived from turmeric has been used daily in India for thousands of years and was first cultivated in Harappa as early as approximately 3000 B.C.…”
Section: Biomedical Applications Using Dfnsmentioning
confidence: 99%